Behind the Perfect Uniform: The Role of Body image and Self-esteem in Predicting Restrained eating among Cadets at a Semi-military School in Tegal - Robiano Galih Pradana; Tesa Nurul Huda; Rr. Setyawati; Gisella Arnis Grafiyana (Universitas Katolik Soegijapranata, 2025)
Restrained eating is strongly suspected to be a manifestation of the underlying psychological stress contributing to the problem of non-ideal nutritional status among cadets in a semi-military government institute. Therefore, this study aims to analyze and prove the significant influence of cadetts' body image and self-esteem on the tendency for restrained eating in this semi-military school environment. The sampling technique used was probability sampling with sample consisted of 136 participants from a total population of 218. Research data was collected using the restrained eating scale, the body image scale, and the Rosenberg self-esteem scale (RSES). The results of multiple linear regression analysis using SPSS showed that: (1) Body image and self-esteem collectively have a significant influence on restrained eating (p= 0.00; F=8.834); (2) Body image individually does not have a significant influence on restrained eating (p= 0.986; β= -0,042); and (3) Self-esteem individually has a significant influence on restrained eating (p= 0.00; β= 0,73). Authors highlight the complex psychological dynamics that influence eating behavior within a semi-military educational environment